SEGMENTATION, TARGETING AND POSITIONING ANALYSIS OF BEN ALI MORINGA LEAF TEA (Case Study: CV. Atlantic) - MITHA DILASARY (Syarif Hidayatullah State Islamic University Jakarta, 2023)
This study aims to analyze the segmentation, targeting, positioning strategy at CV. Atlantic. This research is a qualitative study that provides an interpretation of the data found in the field and is descriptive in explaining the object of research. This research uses primary data collection techniques and secondary data. Primary data is obtained from observation, interviews using questionnaires directly with respondents and documentation. Secondary data is obtained from journals, books and company records. In this study, there is one sample, namely the owner or Director of CV. Atlantic. Qualitative research data analysis techniques use stages, namely data reduction, data presentation or display and conclusion drawing. Based on the results of the research and discussion that has been analyzed, it can be concluded that the application of segmentation, targeting, positioning strategies at CV. Atlantic has not been maximized, namely in the segmentation aspect, namely in demographic and behavioral segmentation. In targeting, namely in the target market determination pattern and target market determination strategy. Meanwhile, positioning is on product attributes.Keywords: Segmentation, Targeting, Positioning